Flow diverters for ruptured posterior circulation perforator aneurysms: multicenter experience and literature review. (12th February 2020) - Da Ros, Valerio; Diana, Francesco; Sabuzi, Federico; Malatesta, Emanuele; Sanna, Antioco; Scaggiante, Jacopo; Di Giuliano, Francesca; Gandini, Roberto; Floris, Roberto; Ruggiero, Maria
Abstract : Background: The management of ruptured posterior circulation perforator aneurysms (rPCPAs) remains unclear. We present our experience in treating rPCPAs with flow diverter stents (FDs) and evaluate their safety and efficacy at mid- to long-term follow-up. A diagnostic and therapeutic algorithm for rPCPAs is also proposed. Methods: We retrospectively analyzed data from all consecutive patients with rPCPAs treated with FDs at our institutions between January 2013 and July 2019. Clinical presentations, time of treatments, intra- and perioperative complications, and clinical and angiographic outcomes were recorded, with a mid- to long-term follow-up. A systematic review of the literature on rPCPAs treated with FDs was also performed. Results: Seven patients with seven rPCPAs were treated with FDs. All patients presented with an atypical subarachnoid hemorrhage distribution and a low to medium Hunt–Hess grade. In 29% of cases rPCPAs were identified on the initial angiogram. In 57% of cases, FDs were inserted within 2 days of the diagnosis. Immediate aneurysm occlusion was observed in 14% of the cases and in 71% at the first follow-up (mean 2.4 months). At mean follow-up of 33 months (range 3–72 months) one case of delayed ischemic complication occurred. Six patients had a modified Rankin Scale (mRS) score of 0 and one patient had an mRS score of 4 at the latest follow-up. Conclusions: The best management for rPCPAs remains unclear, but FDs seem to have lower complication rates than other treatment options. Further studies with larger series are needed to confirm the role of FDs in rPCPA.